Elementos constituintes da identidade docente na área de ensino de ciências e matemática - Silva, Marcos Paulo (Universidade Federal de São Carlos, 2026)
The undergraduate teacher training programs seek, through their curricula, to promote initial training for the teaching profession. However, due to the low interest in the teaching career, it is still common for undergraduates and graduates to migrate to other areas in detriment of teaching, factors that may be related to working conditions and the low recognition of the profession by society. Regarding Natural Sciences and Mathematics, there have been significant advances that allowed for greater visibility for the area with the creation of Graduate Programs and, in certain cases, curriculum reformulations. Furthermore, Teaching Incentive Programs have emerged in recent years aiming for greater attractiveness for the teaching career, through teaching practice even during initial training, as in the case of the Institutional Program of Scholarships for Initiation to Teaching (PIBID) and the Pedagogical Residency Program (PRP). In this sense, based on Marcelo García (1999), Nóvoa (1992) and Gatti (2012), who address the issue of teacher training; Huberman (1992) who studies the stages of the teaching career and, Dubar (2005) who investigates Teacher Identity, this work sought, through a bibliographic research and, subsequently, the use of Discursive Textual Analysis, to verify which are the most recurrent elements for the initial training and also, for the construction of the Teacher Identity of undergraduates from courses focused on natural sciences and mathematics, in the context of theses and dissertations defended in Programs in the area of Science teaching. Results indicate that some factors appear as more significant for the professional choice for teaching, such as family and teacher influences, as well as the individual life trajectories of each individual. It was also observed, through the analyses of the dissertations and theses, that the specificity of the area of natural sciences and mathematics was not located, indicating that, despite there being identification with the area of study, this is not the only preponderant factor in the choice of the teaching career.
Components of teacher identity in the field of science and mathematics education
Keywords: Identidade Docente; Carreira docente; Ciências da natureza e matemática; Teacher Identity; Teaching career; Natural sciences and mathematics; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade